The Effects of Oil Property and Inclination Angle on Oil–Water Core Annular Flow Through U-Bends - Jiang, Fan (2017)
Understanding the impact mechanism of the oil properties and the bend geometric parameters on oil–water core annular flow in bends is of great importance for the design and operation of bend pipelines. To address this, the oil–water core annular flow through U-bends is analyzed numerically, by using the volume of fluid technique together with the continuum surface stress method. A good match is observed between the numerically simulated phase contours and those taken from reported experiments. The influence of the inclination angle, the inlet diameter ratio, oil properties, and the pipe materials on the hydrodynamics is investigated together with the fouling characteristics of core annular flows. Through the numerical simulations, the flow in a range of operating conditions has been determined, together with the influence of geometric parameters and pipe material.